2022
DOI: 10.1038/s41419-022-04953-z
|View full text |Cite
|
Sign up to set email alerts
|

DNAJC24 is a potential therapeutic target in hepatocellular carcinoma through affecting ammonia metabolism

Abstract: Evolutionarily conserved heat shock proteins are involved in the heat shock response of cells in response to changes in the external environment. In normal tissues, heat shock proteins can help cells survive in a rapidly changing environment. Likewise, in malignant tumors heat shock proteins may help tumor cells cope with external stresses as well as the stress of treatment. In this way they become accomplices of malignant tumors. Here we demonstrated for the first time that high expression of DNAJC24 (a heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…33 Autophagy is generally considered to be a mechanism that allows cancer cells to maintain cellular homeostasis under either normal or stressful conditions. 34 Accumulating evidence has indicated that autophagy plays a complex role in cancer cell motility and invasion during tumor metastasis. 23 Depending on the tumor microenvironment, autophagy has been reported to play pro-and anti-metastasis roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Autophagy is generally considered to be a mechanism that allows cancer cells to maintain cellular homeostasis under either normal or stressful conditions. 34 Accumulating evidence has indicated that autophagy plays a complex role in cancer cell motility and invasion during tumor metastasis. 23 Depending on the tumor microenvironment, autophagy has been reported to play pro-and anti-metastasis roles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCSK9 was involved in the development of autophagy, as discovered in ischemic myocardial cells from a report in 2018 33 . Autophagy is generally considered to be a mechanism that allows cancer cells to maintain cellular homeostasis under either normal or stressful conditions 34 . Accumulating evidence has indicated that autophagy plays a complex role in cancer cell motility and invasion during tumor metastasis 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Guo and his colleagues showed that high expression of DNAJC24 (HSP40 Member C24, a heat shock protein) occurs in hepatocellular carcinoma patients with shortened life span and that the transcription of DNAJC24 is regulated by HSF2 [ 94 ] ( Table 1 ).…”
Section: Hsf2 Affects Cancer Development and Progressionmentioning
confidence: 99%
“…Next, they performed the correlation analysis using the Cancer Genome Atlas (TCGA) database and determined that HSF2 expression is positively correlated with DNAJC24 higher than other HSFs. Additionally, HSF2 expression was higher in hepatocellular carcinoma tissues than in para-cancerous tissues, and the HSF2 expression level increased with tumor stage [ 94 ]. These data indicate that the HSF2-DNAJC24 pathway is also involved in the HSF2-mediated mechanism of hepatocellular carcinoma survival or progression.…”
Section: Hsf2 Affects Cancer Development and Progressionmentioning
confidence: 99%
“…10 Our previous study has demonstrated for the first time that DNAJC24 played an important role in tumor cell proliferation. 11 However, the role of DNAJC24 and the molecular mechanism in tumor progression deserve further investigation. Therefore, exploring the possibility of DNAJC24 as a novel biomarker and fully understanding the function of DNAJC24 in LUAD progression are crucial.…”
Section: Introductionmentioning
confidence: 99%